Multisystem Mitochondrial Disease Associated With a Mare m.10000G>A Mitochondrial tRNAGly (MT-TG) Variant - Yang, Haiyan; Zhang, Victor Wei; Ai, Liang; Gan, Siyi; Wu, Liwen (Frontiers in Neurology, 2022)
Background Mitochondrial diseases are clinically heterogeneous, can occur at any age, and can manifest with a wide range of clinical symptoms. They can involve any organ or tissue, characteristically involve multiple systems, typically affecting organs that are highly dependent on aerobic metabolism, and making a definitive molecular diagnosis of a mitochondrial disorder is challenging. Methods Clinical data of the proband and his family members were gathered in a retrospective study. Whole-exome sequencing and full-length sequencing of the mitochondrial genome that were performed on peripheral blood, urine, and oral mucosa cells were applied for genetic analysis. Results In this study, we reported a childhood-onset mitochondrial phenotype in a 13-year-old patient. Analysis of the next-generation sequencing data of the nuclear genome and the full-length sequencing of the mitochondrial genome revealed the rare m.10000G>A variant in MT-TG that was present at variable heteroplasmy levels across tissue types: 32.7% in the blood, 56.15% in urinary epithelial cells, and 27.3% in oral mucosa cells. No variant was found in the peripheral blood of his mother and sister. No pathogenic mutation of nDNA was found. Conclusion Our results added evidence that the de novo m.10000G>A variation in the highly conserved sequence of MT-TG appears to suggest a childhood-onset mitochondrial phenotype in the 13-year-old patient, thus broadening the genotypic interpretation of mitochondrial DNA-related diseases.